A SURVEY ON EFFECTIVE FACTORS ON DEMAND OF CONSUMPTION, CAPITAL AND INTERMEDIATE GOODS - Hamid Toufighi; Azadeh Mehrabian (فصلنامه پژوهش‌های اقتصادی ایران, 2003)
In the analysis of macroeconomic problems and eonomic policies, the survey of import demand function is very important and it has a key role in efficiency and effectiveness of trade policies. Imports and factors affecting it, are playing an important role in the trade balance of each country. This paper presents a new method for estimation of import demand function for Iran during 1958-1998. For empirical test, we use vector auto correlation that shows import, depends positively on oil revenues, GDP without oil and at the same time negatively affects relative prices (The ratio of imported price to domestic price). In addition, we discussed various shocks and their immediate effects on different variables through application of impulse response and variance decomposition and tried to show the effect of changes on variables, and on import demand accordingly.